Oil Price and Financial Sector in Eastern Europe: A Panel Data Investigation - Lavinia Horobet, Alexandra; Maria Vrinceanu, Georgiana; Barsan, Ana-Maria (KnE Social Sciences, 2020)
Our paper investigates the exposure to oil price fluctuations of financial companies listed on stock exchanges from Eastern European countries: Romania, Bulgaria, Hungary, Poland, Czech Republic, Slovakia, Slovenia and Croatia. Using monthly datasets covering the period from February 2010 to February 2018, we examine the relationship between stock prices of these financial companies, oil prices and other macroeconomic variables, such as local stock indices, a European stock index designed to measure the performance of companies from this region (FTSE Europe), an indicator of a country’s international price competitiveness (NEER), interest rates and an indicator of systemic stress, named Composite Indicator of Systemic Stress (CISS). Applying the panel data methodology, our results indicate an unexpected fact. We show that there is a significant exposure of financial companies to the oil price fluctuations. We discover that in the financial sector, high oil prices may have indeed positive effects on the stock prices. The price of oil has a higher impact on the stock prices of financial companies than we expected and it proved be a risk factor for this sector. Our results indirectly highlight the pervasive exposure of economies from the region to risk factors through the financial sector channels, which raises serious challenges from the perspective of macroeconomic and financial policies. Keywords: oil price, financial sector, panel data analysis